Stereoselective Thioconjugation by Photoinduced Thiol‐ene Coupling Reactions of Hexo‐ and Pentopyranosyl d‐ and l‐Glycals at Low‐Temperature—Reactivity and Stereoselectivity Study. Issue 64 (1st October 2019) - Kelemen, Viktor; Bege, Miklós; Eszenyi, Dániel; Debreczeni, Nóra; Bényei, Attila; Stürzer, Tobias; Herczegh, Pál; Borbás, Anikó
Abstract: A comprehensive optimization and mechanistic study on the photoinduced hydrothiolation of different d ‐ and l ‐ hexo‐ and pentoglycals with various thiols was performed, at the temperature range of RT to −120 °C. Addition of thiols onto 2‐substituted hexoglycals proceeded with complete 1, 2‐ cis ‐α‐stereoselectivity in all cases. Hydrothiolation of 2‐substituted pentoglycals resulted in mixtures of 1, 2‐ cis ‐α‐ and ‐β‐thioglycosides of varying ratio depending on the configuration of the reactants. Hydrothiolation of unsubstituted glycals at −80 °C proceeded with excellent yields and, except for galactal, provided the axially C2‐S‐linked isomers with high selectivity. Cooling was always beneficial to the efficacy, increased the yields and in most cases significantly raised the stereoselectivity. The suggested mechanism explains the different conformational preferences of the intermediate carbon‐centered radicals, which is a crucial factor in the stereoselectivity of the reactions. Abstract : Three types of acetylated glycals were reacted with various thiols under UV‐irradiation at the temperature range of RT to −120 °C. Cooling proved always beneficial to the reaction efficacy, being −80 °C the optimal temperature in most cases. The low‐temperature thiol‐ene coupling of glycals was found to provide an easy access to 1, 2‐ cis ‐α‐1‐thio‐hexosides up to tetrasaccharides, 1, 2‐ cis ‐α‐ and β‐1‐thio‐pentosides and axially C2‐S‐linked glycomimetics.